The effects of internet and social media use on the work performance of physicians and nurses at workplaces in Palestine - Muna Ahmead; Nida Hamamadeh; Issa abu Iram (BMC, 2022)
Abstract Background The use of internet and social media applications in the workplace has increased dramatically with both beneficial and harmful effects. Their use also appears to affect job performance in the workplace. Aim To assess the beneficial and harmful effects of internet and social media application use in the workplace, and on the work performance of health professional in the major 4 referral hospitals in the cities of Hebron and Bethlehem. Method A cross-sectional study was conducted using self-reported questionnaires: a work-related social media questionnaire (WSMQ), and the William Anderson Work Performance Scale. The sample of the study included 409 participants (169 physicians and 240 nurses). Results The Pearson correlation test showed a weak positive statistically significant relationship between the WSMQ and William Anderson Work Performance Scale. The findings revealed that the overall mean score for the WSMQ was high (mean score 3.57), and the higher mean was for the beneficial WSMQ compared with the harmful WSMQ. The mean for the William Anderson Work Performance Scale was moderate performance (3.35). The higher mean was for Organizational Citizenship Behavior-Individual (OCBI), followed by In Role Behavior (IRB). Conclusion Palestinian healthcare professionals should be encouraged to use internet and social media applications to improve health outcomes, and provide health information to the community rather than simply using these tools for communication. Administrative staff and policy makers in Palestinian hospitals should regulate the use of internet and social media applications in hospitals by developing a clear policy on this topic for the workplace.